Morphological and structural characteristics of Urochloa decumbens Stapf. deferred pasture grazed by heifers under two periods of protein-energy supplementation - Pedro Henrique Ferreira da Silva; Carlos Augusto Brandão de Carvalho; Pedro Malafaia; Felipe Zumkeller Garcia; Rondineli Pavezzi Barbero; Robson Leandro Ferreira (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to evaluate the morphological and structural characteristics of deferred Urochloa decumbens Stapf. ‘Basilisk’ grazed by Nellore heifers under two periods of protein and energy supplementation (PES). The experiment was carried out from Jun 21 to Nov 15, 2016, under a completely randomized design and two PES periods (55 [P55] and 147 [P147] days). Forage mass (FM), leaf blade dry mass (LBDM), stem dry mass (SDM), dead material dry mass (DMDM), canopy height (CH), and forage bulk density (FBD) were evaluated. Data were analyzed by the SAS® PROC MIXED procedure and treatment means were compared with the Student's t test (p < 0.05). LBDM was higher for P147 heifers after 21, 84, and 126 days of grazing, similar to those observed after 63 days, and was higher for P55 heifers at 42, 105, and 147 days of grazing. SDM was lower for P147 heifers after 21, 42, 105, and 126 days, and similar in the other grazing periods. Protein and energy supplementation for heifers over 147 days resulted in a lower stem mass of U. decumbens Stapf. ‘Basilisk’ deferred pastures.